2006
DOI: 10.1016/j.meatsci.2006.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to increase consumer trust in meat as a safe and wholesome food

Abstract: This paper focuses on the effect of information about meat safety and wholesomeness on consumer trust based on several studies with data collected in Belgium. The research is grounded in the observation that despite the abundant rise of information through labelling, traceability systems and quality assurance schemes, the effect on consumer trust in meat as a safe and wholesome product is only limited. The overload and complexity of information on food products results in misunderstanding and misinterpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 23 publications
3
40
0
4
Order By: Relevance
“…A three segment model was derived, which reflected a good trade-off between model fit and parsimony. The three segment model was also in line with McCarthy and Henson (2005) and Gellynck et al (2006) who also identified three segments. To derive the segments, a finite-mixture model was estimated.…”
Section: Assessment Of Trust Levelssupporting
confidence: 73%
“…A three segment model was derived, which reflected a good trade-off between model fit and parsimony. The three segment model was also in line with McCarthy and Henson (2005) and Gellynck et al (2006) who also identified three segments. To derive the segments, a finite-mixture model was estimated.…”
Section: Assessment Of Trust Levelssupporting
confidence: 73%
“…Safety and quality were also relatively important with food safety clearly an important consideration for consumers when buying meat. Meanwhile, Gellynck et al [28] investigated which attributes of traceability for Belgian consumers are the most important. They distinguished between functional and process attributes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These experiences in Europe offer lessons on, for instance, the importance of open communication and transparency. As a result of these experiences, the provision of information and the development of quality assurance programs do not increase consumer confidence in such arenas as meat safety and animal welfare (Gellynck et al, 2006). It is recognized that consumer trust is based on both objective rational information together with subjective or emotional inputs (Gellynck et al, 2006).…”
Section: The Challenge: New Models For Building Trustmentioning
confidence: 99%
“…As a result of these experiences, the provision of information and the development of quality assurance programs do not increase consumer confidence in such arenas as meat safety and animal welfare (Gellynck et al, 2006). It is recognized that consumer trust is based on both objective rational information together with subjective or emotional inputs (Gellynck et al, 2006). Again, the critical focus needs to be on trust: for example, challenges to Danish-British bacon supply chain were addressed successfully by trust-based marketing meeting consumer expectations of safe bacon from production systems that "are environmentally friendly and conform to animal welfare" (Lindgreen, 2003).…”
Section: The Challenge: New Models For Building Trustmentioning
confidence: 99%